2022
DOI: 10.1002/ajoc.202100757
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐DMSO‐Promoted Oxygenation of Indoles: Synthesis of Isatin and Isoindigo

Abstract: Oxygenation/oxidative self-coupling of indole are performed to obtain isatin and isoindigo in the absence of metal catalysts. Iodine-DMSO is used to synthesize isatin whereas Iodine-DMSO-K 2 S 2 O 8 combination is used for isoindigo synthesis directly from indole in a single step. Though several methods are known for isatin synthesis from indole, most of them use large quantity of oxidants or metal catalyzed. Moreover, the primary existing process for the synthesis of isoindigo is the condensation of isatin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…General procedure for the synthesis of substrate 1 2.1 General procedure 1 for the synthesis of 9H-fluoren-9-one 9H-fluoren-9-one was synthesized according to the previous report. 1 20.0 mmol) and KI (0.664 g, 4.00 mmol) were mixed in acetonitrile (60 mL).…”
Section: General Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…General procedure for the synthesis of substrate 1 2.1 General procedure 1 for the synthesis of 9H-fluoren-9-one 9H-fluoren-9-one was synthesized according to the previous report. 1 20.0 mmol) and KI (0.664 g, 4.00 mmol) were mixed in acetonitrile (60 mL).…”
Section: General Informationmentioning
confidence: 99%
“…On the basis of a literature search, there are a vast number of reported synthetic protocols to construct isoindigos, for example, acid-catalyzed condensation of isatins with oxindoles, 12 gold-catalyzed dimerization of 3-diazooxindoles, 13 palladium-catalyzed cyclization, 14 dimerization of oxindoles using thionyl chloride (SOCl 2 ) 15 or N -chlorosulfenylsuccinimide, 16 sodium iodide promoted dimerization of oxindoles, 17 visible-light-promoted, iodine-mediated dimerization of 3-diazooxindoles, 18 iron-catalyzed dimerization of isatins, 19 and dimerization of indoles promoted by a combination of I 2 /DMSO/K 2 S 2 O 8 . 20…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
See 1 more Smart Citation
“… [10–13] Recently Lombardi et al reported an efficient Mn‐containing artificial enzyme promoted indole oxidation selectively at 3‐position [14] . P. K. Baruah reported I 2 ‐DMSO promoted oxygenation of Indoles to directly obtain Isatin and IsoIndigo [15] . Pd catalyzed [16–19] and transition‐metal‐free [20–22] acetoxylation of substituted indoles with diacetoxy iodobenzene as external oxidant have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[14] P. K. Baruah reported I 2 -DMSO promoted oxygenation of Indoles to directly obtain Isatin and IsoIndigo. [15] Pd catalyzed [16][17][18][19] and transition-metal-free [20][21][22] acetoxylation of substituted indoles with diacetoxy iodobenzene as external oxidant have been studied.…”
Section: Introductionmentioning
confidence: 99%